Impact of Alternatively Treated Greywater on Raphanus sativus Development in Tacna, Peru (Journal SCIENCEVOLUTION, 2025)
The increasing water scarcity in arid regions such as Tacna, Peru, necessitates the development of sustainable alternatives for utilizing non-conventional water resources. This study evaluated the efficiency of greywater treatment using alternative technologies based on natural coagulants (cassava and sweet potato starch) and orange peel activated carbon, aiming to determine their effect on water quality and Raphanus sativus growth. A completely randomized design and statistical analyses (ANOVA and Tukey's test) were employed to assess physicochemical (pH and turbidity) and biological parameters (germination percentage and radicle length). Results demonstrated significant turbidity reductions exceeding 85%, with sweet potato starch at 25 ml achieving the highest efficiency (86.67 %), without altering pH, which remained within a neutral range (7.1–7.8). Furthermore, all treated seeds exhibited 100 % germination and significant radicle development, with 15 % cassava starch proving the most favorable treatment. These findings validate the viability of these methods as sustainable, cost-effective, and low-environmental-impact solutions, promoting their reuse in agricultural contexts. Expanding the study to other water sources and crops is recommended.
Keywords: Greywater; Natural Coagulants; Starch; Cassava; Sweet potato; Activated Carbon; Raphanus Sativus; Germination